MINERALOGICAL, GEOCHEMICAL AND PETROPHYSICAL CHARACTERIZATION OF SHALES AND MUDSTONES OF CENTRAL SARAWAK, MALAYSIA - MOHAMED KHAIR, WALAA ELNASIR IBRAHIM (2021)
Unconventional organic-rich shales are considered to be giant resources of natural gas